Trust and compliance: Milieu-specific differences in social cohesion during the COVID-19 pandemic in Germany - Schröder, Tim; Speer, Anne; Sachweh, Patrick; Groh-Samberg, Olaf (Frontiers in Sociology, 2022)
As a response to the COVID-19 pandemic, an increase in social cohesion was observed during the first wave and its aftermath. A closer look reveals heterogeneous responses regarding aspects of cohesion—such as trust in others and compliance with containment measures—that differ by individual socioeconomic and cultural characteristics. How these characteristics affect social cohesion in combination is rarely investigated. Therefore, we introduce the concept of social milieus, which addresses the interrelation of socioeconomic and cultural characteristics on the level of social groups, into the international debate. While previous studies have applied this concept to the analysis of social cohesion during the pandemic, they exhibit theoretical and empirical shortcomings. Hence, we develop a new theoretical model of social milieus and an empirical typology using the German sample of the European Social Survey. This typology is matched with data from the Research Institute Social Cohesion (RISC) for a milieu-specific analysis of social cohesion. Results show considerable heterogeneity in social cohesion during the first wave of the pandemic in Germany. Three social milieus with potentially conflicting modes of social cohesion regarding trust and compliance stand out while other milieus are less diverging as presumed in the literature. These modes can be interpreted as emerging from a combination of the milieus' socioeconomic position and basic human values. Thus, the new theoretical model and empirical typology of social milieus contribute to the understanding of how social cohesion has been contested between social milieus early in the pandemic.